2019
DOI: 10.3389/fncel.2018.00528
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Altered Developmental Pathways in Human Juvenile HD iPSC With 71Q and 109Q Using Transcriptome Profiling

Abstract: In Huntington disease (HD) subtle symptoms in patients may occur years or even decades prior to diagnosis. HD changes at a molecular level may begin as early as in cells that are non-lineage committed such as stem cells or HD patients induced pluripotent stem cells (iPSCs) offering opportunity to enhance the understanding of the HD pathogenesis. In addition, juvenile HD non-linage committed cells were previously not directly investigated in detail by RNA-seq. In the present manuscript, we define the early HD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…Indeed, studies examining neurogenesis using mouse HD stem cells have given conflicting results showing that mutant HTT both impairs neurogenesis [21] and promotes it [13,22]. Efforts to examine the impact of mutant HTT on neurodevelopment and neurogenesis using human pluripotent stem cells (hPSCs) having been similarly unclear [18,19,[23][24][25][26] (reviewed in [27]). Mutant HTT was shown to impact early ectodermal development, reflected in an altered phenotypic signature, in an in vitro model of neurulation [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies examining neurogenesis using mouse HD stem cells have given conflicting results showing that mutant HTT both impairs neurogenesis [21] and promotes it [13,22]. Efforts to examine the impact of mutant HTT on neurodevelopment and neurogenesis using human pluripotent stem cells (hPSCs) having been similarly unclear [18,19,[23][24][25][26] (reviewed in [27]). Mutant HTT was shown to impact early ectodermal development, reflected in an altered phenotypic signature, in an in vitro model of neurulation [28].…”
Section: Introductionmentioning
confidence: 99%
“…Mutant HTT was shown to impact early ectodermal development, reflected in an altered phenotypic signature, in an in vitro model of neurulation [28]. Based on transcriptional analyses of hPSCs [26], neural progenitors [23,25], and neurons [24], a number of studies 2/26 have also suggested that mutant HTT impairs neural progenitor differentiation and delays neuronal maturation. However, assessment of cortical neurogenesis showed no effect of mutant HTT on the quantity or timeline of differentiation of deep and upper layer cortical neurons [24].…”
Section: Introductionmentioning
confidence: 99%
“…Results Reference HD iPSCs-MSNs -elevated caspase activity upon growth factor deprivation [12] HD iPSC-MSN -neuroprotective effect of CGS21680 and APEC therapeutic potential [18] HD iPSC-NPCs -higher levels of FOXO1 and FOXO4 elevated proteasome activity [19] iPSC-GABA + neurons -under treatment with memantine reversal of HD pathologic events [20] HD monkey iPSC-astrocytes -detection of numerous HD related pathologies mHTT aggregates, inefficient glutamate clearance, suppression of mitochondrial function, abnormal electrophysiology [21] Corrected HD iPSC-NPCs -after transplantation into mice model survival and differentiation of cells into the GABAergic neurons [22] iPSC-NSCs -after bilateral transplantation into mice striatum improved locomotor function [33] mice HD iPSCs/human HD iPSCs -dysregulation of ERK signaling, β-catenin phosphorylation, SOD1 accumulation and p53 expression [34] Juvenile HD-iPSCs -high number of significantly dysregulated mRNAs [35] HD iPSC-MSN -increased calcium SOC activity; treatment by quinazoline derivative -EVP4593 led to reduced activity of SOC currents and normalization of calcium transport [23] HD monkey iPSC-NPCs -under treatment with memantine, Rilizole and Methylene blue the most potent anti-apoptotic drug was Rilizole; the most effective in reduction of mTT aggregates was Methylene blue [36] Corrected HD monkey iPSC-GABA + neurons -after transplantation into mice striatum longer lifespan of HD mice model; improved behavioral and locomotor function [37] Zhang et al [12] were among the first authors to generate an iPSC-derived HD model. The researchers developed iPSCs from an HD patient displaying 72 CAG repeats, which were used to generate striatal neurons susceptible to cellular damage with typical characteristics of HD, such as mHTT aggregation and decreased concentrations of glutamate transporters and BDNF.…”
Section: Model Cell Typementioning
confidence: 99%
“…The presence of these effects in pluripotent cells indicates that the pathological processes begin during early embryonic development. Another group also investigated early molecular pathologies in HD-iPSCs, but with the goal of identifying the pathological, transcriptional changes in juvenile HD-iPSCs, which occur during the neurodevelopment of HD [35]. These authors used the RNA-seq method to study the transcriptional profiles of 6 human juvenile HD-iPSC lines with 71 and 109 CAG repeats.…”
Section: Model Cell Typementioning
confidence: 99%
See 1 more Smart Citation